Study on the Status of Avifaunal Diversity in Social Forestry Division Bareilly, Uttar Pradesh - Tomar, Virat Singh; Chouksey, Sandeep; Kerketta, Neeta Shweta (Asian Journal of Biological and Life Sciences, 2017)
The study was conducted in social forestry division Bareilly, Uttar Pradesh from 2013 to 2015. The presented paper involved a survey of bird species and preparing the checklist in the surveyed area. Atotal of 104 different bird species belongs to 48 families were recorded in the study area. Of which 80 species were resident, followed by 21 migratory and 3 were resident migratory. Of 104, 36 were insectivores followed by 27 carnivorous, 22 omnivores, 6 granivore, 5 fruigivore, 6 carnivorous, insectivorous and 2 were insectivorous, fruigivores. Of 104 bird species recorded maximum (94) was the least concern status, 6 were nearly threatened, 2 were vulnerable, 2 were endangered and 1 was critically endangered in IUCN red list category. Birds play important role in an agriculture ecosystem and maintain the ecological balance. The presence of birds in an area defines the wealth of ecosystem. For maintaining the bird diversity it is recommended to limit the use of pesticides and fertilizers. Planting the trees in agriculture fields would lead the increase of bird's population in the area.
Keywords: Avifaunal; Biodiversity; Birds; Survey